Development of a Community-engaged Research Training Workshop for Clinician-Scientists and Early-stage Investigators - Emily P. Courtney; Cathy D. Meade; Clement K. Gwede; Veronica Barrios-Monroy; Isabel C. Scarinci; Usha Menon; Monica Baskin; David Schwartz; Monica E. Peek; Anissa I. Vines; Z’Kera Peoples; Jamboor K Vishwanatha; et al. (Journal of Cancer Education, 2026)
Community-engaged research (CEnR), a collaboration between academics and community partners, is an effective approach in addressing the social drivers of health (SDOH) and health disparities in local communities. Yet, CEnR training is often not a standard component of training programs in research or clinical programs. To meet the need for CEnR training, we developed and implemented a workshop to increase CEnR knowledge and skills among clinician-scientists and early-stage investigators (ESIs), and create opportunities for ongoing mentorship and professional development. In this manuscript, we discuss the organization of this workshop, learning objectives, supporting activities, and follow-up methods to facilitate a successful and engaging training experience. The workshop was developed through collaborative efforts with experts in CEnR, Community-Based Participatory Research (CBPR), cancer disparities, and SDOH. The workshop focused on (1) an introduction to CEnR and the opportunity for attendees to develop their own CEnR research ideas; (2) varied presentations, interactive activities, experiential learning, and discussion topics to fulfill the workshop’s learning objectives; (3) year-long opportunities for professional development and continued mentorship; and (4) evaluations of the workshop. Twenty-four ESIs and 11 clinician-scientists participated in the workshop. Using survey methods and descriptive statistics, the workshop was evaluated positively by participants. This manuscript provides guidance for both in-person and virtual workshop formats, from inception to implementation, and recommendations for other workshop facilitators. The impact of these workshops has the potential to have positive downstream implications for community-engaged research.

The cannabinoid receptor 2 is an in vivo receptor of bisphenol A during bone formation - Matthew J. Dubuisson; Carol K. Cox; Jasleen Kaur; McLean H. Williamson; Wilson K. Clements; Madelyn K. Logan; Jerry D. Monroe; Yann Gibert (Journal of Hazardous Materials, 2026)

Protective antibodies against enterotoxigenic Escherichia coli are generated from heat-labile toxoid vaccination and exhibit subject- and vaccine-specific diversity - Milton Maciel; Jordan C. Scott; Robin L. Baudier; John D. Clements; Renee M. Laird; Ramiro L. Gutiérrez; Chad K. Porter; Elizabeth B. Norton (Medical Microbiology and Immunology, 2025)
Heat-labile toxin (LT) from enterotoxigenic Escherichia coli (ETEC) is an important pathogenic protein. Anti-LT antibodies (Abs) induced by vaccination can neutralize the toxin and potentially prevent diarrheal secretion from ~ 60% of ETEC strains expressing LT. However, only superficial investigation of the anti-toxin response is usually conducted in clinical trials. Here, we utilized human serum samples from two clinical trials performed to assess safety, immunogenicity and protection in a controlled human infection model with a LT + ST + CFA/I + H10407 ETEC strain. These Phase 1 and Phase 2b clinical trials explored a prototype ETEC adhesin (CfaE) and a chimeric adhesin-toxoid protein (dscCfaE-CTA2/LTB5) delivered intradermally or transcutaneously with a mutated form of LT (mLT) as an adjuvant. Serum samples were tested for antigen-specific IgG or IgA Abs by immunoblot, enzyme-linked immunosorbent assay (ELISA), or functional neutralizing Abs using LT holotoxin, LTA or LTB subunits. Abs to both LT subunits were present, but the response to each was altered by vaccine formulation, dose, and delivery routes as well as subject. The anti-LT IgG response correlated best to neutralizing antibodies and protection from H10407 controlled challenge when compared to other measures including serum IgA or anti-fimbriae (CfaE) Abs. In addition, our results helped to explain cohort attack rate differences in naïve unvaccinated participants and we found higher anti-LTA IgG post-challenge significantly related to ETEC severity score. Thus, strategies generating and measuring immunity to the complete AB 5 structure of LT and subunits are better determinant of assessing protective immunity against LT + or LT + ST + ETEC diarrheal secretion in humans.

Evaluation of a Multi-Site Cancer Health Disparities Research Training Program for Underrepresented Undergraduate and Medical Students - Lakeshia Cousin; Z’Kera Peoples; Vivekka Suppiah; Jiannong Li; Gwendolyn P. Quinn; Ursula Martinez; Arnold H. Zea; Cathy D. Meade; Clement K. Gwede; Fern Tsien; Jovanny Zabaleta; Richie Reich; et al. (Journal of Cancer Education, 2025)

Leopards on the edge: Assessing population status, habitat use, and threats in Southeast Asia - S. Rostro-García; J.F. Kamler; R. Sollmann; G. Balme; R. Sukmasuang; A. Godfrey; S. Saosoong; K. Siripattaranukul; S. Suksavate; W. Thomas; R. Crouthers; V. In; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Association of Preventive Care Attitudes and Beliefs with Colorectal Cancer Screening History among African American Patients of Community Health Centers - John S. Luque; Gebre-Egziabher Kiros; Matthew Vargas; Deloria R. Jackson; Olayemi O. Matthew; Tifini D. Austin; Rima Tawk; Askal A. Ali; Cynthia M. Harris; Kristin Wallace; Clement K. Gwede (Journal of Cancer Education, 2023)

The world's largest omnivore is a fish - M. G. Meekan; P. Virtue; L. Marcus; K. D. Clements; P. D. Nichols; A. T. Revill (Ecology, 2022)
The evolution of very large body size requires a ubiquitous and abundant source of food. In marine environments, the largest animals such as whale sharks are secondary consumers that filter feed on nekton, which is plentiful, although patchy. Consequently, feeding in coastal environments requires cost‐efficient foraging that focuses on oceanographic features that aggregate both nektonic prey and marine debris such as floating macroalgae. Consumption of this algae could present an energetic challenge for these animals, unless some component can be digested. Here, we use a multi‐technique approach involving amino acid compound‐specific stable isotope analysis (CSIA) and fatty acid analysis to determine the trophic level of whale sharks and to identify likely items in the diet. CSIA analyses showed that the species has a trophic level consistent with omnivory. Fatty acid profiles of whale shark tissues, feces and potential prey items suggest that the floating macroalgae, Sargassum , and its associated epibionts is a significant source of food. Although this overcomes the energetic challenge of consumption of floating algae, this mode of feeding and the need to focus on oceanographic features that aggregate prey also increases the threat to the species posed by pollutants such as plastic.

Improving Multi-site Interaction Through Remote Learning Technology: Report from a Training Program to Increase Underrepresented Undergraduate and Medical Students in Health Disparities Research - Z’Kera Sims; Lakeshia Cousin; Vivekka Suppiah; Nathanael Stanley; Jiannong Li; Gwendolyn Quinn; Ursula Martinez; Arnold H. Zea; Vani N. Simmons; Cathy D. Meade; Fern Tsien; Clement K. Gwede (Journal of Cancer Education, 2022)

Cancer disparities in the context of rurality: risk factors and screening across various U.S. rural classification codes - Kelly A. Hirko; Huiwen Xu; Laura Q. Rogers; Michelle Y. Martin; Siddhartha Roy; Kimberly M. Kelly; Shannon M. Christy; Kimlin Tam Ashing; Jean C. Yi; Marquita W. Lewis-Thames; Cathy D. Meade; Qian Lu; et al. (Cancer Causes & Control, 2022)

Neotropical Anacardiaceae (cashew family) - John D. Mitchell; Susan K. Pell; Julien B. Bachelier; Emily J. Warschefsky; Elizabeth M. Joyce; Laura Calvillo Canadell; Cíntia Luíza da Silva-Luz; Clement Coiffard (Brazilian Journal of Botany, 2022)
Anacardiaceae is an ecologically and economically important plant family of about 200 species in 32 genera in the Neotropics. The family is particularly diverse in leaf architecture and fruit morphology, making it a model family to study the evolution of structural diversity as it correlates with lineage diversification. This fruit diversity is the primary reason 11 of the Neotropical genera are monotypic and that so many genera are recognized in the Anacardiaceae. The economic value of the family is driven by the global markets for cashews, mangoes, and pistachios, but there is great potential value in its medicinal properties. At least 10 Neotropical genera cause contact dermatitis, which is a rich area for research in the family. Here presented is a review of the systematics and structural diversity of the family. Particular attention is given to the morphology, economic botany, paleobotany, ecology, and taxonomy of native and naturalized genera. Keys to Neotropical Anacardiaceae subfamilies and genera are provided along with descriptions of native genera.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate change in the context of whole-farming systems: opportunities for improved outreach - R. S. Clements; S. K. Birthisel; A. Daigneault; E. Gallandt; D. Johnson; T. Wentworth; M. T. Niles (Climatic Change, 2021)
Climate change poses a challenge to farming systems worldwide. However, existing research suggests that farmers and those providing outreach may have different climate change perspectives, and there is little understanding of how farmers prioritize climate change compared with other aspects of their farming system. To compare how farmers and outreach professionals in northern New England consider climate change within the context of whole-farming systems, we conducted mental modeling interviews with 33 farmers and 16 outreach professionals. Despite being primed to consider climate during the interviews, only 24% of farmers and 25% of outreach professionals included climate in their mental models. Key differences arose in both group’s perceptions of weather: outreach professionals focused on connections between good weather and biophysical factors, while farmers drew additional connections to factors like quality of life and overall farm success . Social factors including community well-being , public education , and farm success were significantly more likely to be included ( P < 0.05), and in some cases were more influential, in farmer models compared to outreach professional models. We conclude that farmer participants did not perceive climate to be a central factor of their farming systems, and valued human and social dimensions more highly than outreach professionals perceived. These factors may warrant special consideration in efforts to make outreach meaningful to local contexts, along with framing climate change within its broader relationship to other farming system aspects. Interdisciplinary teams may be helpful in developing outreach approaches that fully contextualize climate change within farmers’ complex whole-farm management perspectives.

20 Years Later: Continued Relevance of Cancer, Culture, and Literacy in Cancer Education for Social Justice and Health Equity - Cathy D. Meade; Nathanael B. Stanley; Dinorah Martinez-Tyson; Clement K. Gwede (Journal of Cancer Education, 2020)

Use of standardized methods to improve extinction‐risk classification - Caitlin C. Mothes; Stephanie L. Clements; Dishane K. Hewavithana; Hunter J. Howell; Aaron S. David; Nicole D. Leventhal; Christopher A. Searcy (Conservation Biology, 2020)
Standardized classification methods based on quantifiable risk metrics are critical for evaluating extinction threats because they increase objectivity, consistency, and transparency of listing decisions. Yet, in the United States, neither federal nor state agencies use standardized methods for listing species for legal protection, which could put listing decisions at odds with the magnitude of the risk. We used a recently developed set of quantitative risk metrics for California herpetofauna as a case study to highlight discrepancies in listing decisions made without standardized methods. We also combined such quantitative metrics with classification tree analysis to attempt to increase the transparency of previous listing decisions by identifying the criteria that had inherently been given the most weight. Federally listed herpetofauna in California scored significantly higher on the risk‐metric spectrum than those not federally listed, whereas state‐listed species did not score any higher than species that were not state listed. Based on classification trees, state endemism was the most important predictor of listing status at the state level and distribution trend (decline in a species’ range size) and population trend (decline in a species’ abundance at localized sites) were the most important predictors at the federal level. Our results emphasize the need for governing bodies to adopt standardized methods for assessing conservation risk that are based on quantitative criteria. Such methods allow decision makers to identify criteria inherently given the most weight in determining listing status, thus increasing the transparency of previous listing decisions, and produce an unbiased comparison of conservation threat across all species to promote consistency, efficiency, and effectiveness of the listing process.

Examining the Durability of Colorectal Cancer Screening Awareness and Health Beliefs Among Medically Underserved Patients: Baseline to 12 months Post-Intervention - Shannon M. Christy; Steven K. Sutton; Clement K. Gwede; Enmanuel A. Chavarria; Stacy N. Davis; Rania Abdulla; Ida Schultz; Richard Roetzheim; David Shibata; Cathy D. Meade (Journal of Cancer Education, 2019)

Life‐history traits of the leatherjacket Meuschenia scaber , a long‐lived monacanthid - V. Visconti; E. D. L. Trip; M. H. Griffiths; K. D. Clements (Journal of Fish Biology, 2018)
The present study describes the age and growth of the leatherjacket Meuschenia scaber , a common Australasian monacanthid and valued by‐catch of the inshore bottom trawl fishery in New Zealand. Age was determined from the sagittal otoliths of 651 individuals collected between July 2014 and March 2016 in the Hauraki Gulf of New Zealand. Otolith sections revealed alternating opaque and translucent zones and edge‐type analysis demonstrated that these are deposited annually. Meuschenia scaber displayed rapid initial growth, with both males and females reaching maturity in 1–2 years and 50% of both sexes matured at 1·5 years. Maximum age differed substantially between the sexes, at 9·8 years for males and 17·1 years for females. Growth rate was similar between sexes, although males reached greater mass at age than females in the early part of the lifespan. The length–mass relationship differed significantly between the sexes, with males displaying negative allometric growth and females isometric growth. Female condition was highest in July, declined in August with the onset of spawning and showed a slight peak in January and February, immediately following the spawning season. This study substantially extends the maximum longevity recorded for monacanthids, although males had much shorter lifespans and higher mortality, than females.

Genetic and genomic evidence of niche partitioning and adaptive radiation in mountain pine beetle fungal symbionts - Dario I. Ojeda Alayon; Clement K. M. Tsui; Nicolas Feau; Arnaud Capron; Braham Dhillon; Yiyuan Zhang; Sepideh Massoumi Alamouti; Celia K. Boone; Allan L. Carroll; Janice E. K. Cooke; Amanda D. Roe; Felix A. H. Sperling; et al. (Molecular Ecology, 2017)
Bark beetles form multipartite symbiotic associations with blue stain fungi (Ophiostomatales, Ascomycota). These fungal symbionts play an important role during the beetle's life cycle by providing nutritional supplementation, overcoming tree defences and modifying host tissues to favour brood development. The maintenance of stable multipartite symbioses with seemingly less competitive symbionts in similar habitats is of fundamental interest to ecology and evolution. We tested the hypothesis that the coexistence of three fungal species associated with the mountain pine beetle is the result of niche partitioning and adaptive radiation using SNP genotyping coupled with genotype–environment association analysis and phenotypic characterization of growth rate under different temperatures. We found that genetic variation and population structure within each species is best explained by distinct spatial and environmental variables. We observed both common (temperature seasonality and the host species) and distinct (drought, cold stress, precipitation) environmental and spatial factors that shaped the genomes of these fungi resulting in contrasting outcomes. Phenotypic intraspecific variations in Grosmannia clavigera and Leptographium longiclavatum , together with high heritability, suggest potential for adaptive selection in these species. By contrast, Ophiostoma montium displayed narrower intraspecific variation but greater tolerance to extreme high temperatures. Our study highlights unique phenotypic and genotypic characteristics in these symbionts that are consistent with our hypothesis. By maintaining this multipartite relationship, the bark beetles have a greater likelihood of obtaining the benefits afforded by the fungi and reduce the risk of being left aposymbiotic. Complementarity among species could facilitate colonization of new habitats and survival under adverse conditions.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Erratum to: Development and validation of the biobanking attitudes and knowledge survey-Spanish (BANKS-SP) - Mariana Arevalo; Paul B. Jacobsen; Clement K. Gwede; Cathy D. Meade; Gwendolyn P. Quinn; John S. Luque; Gloria I. San Miguel; Dale Watson; Kristen J. Wells (Journal of Community Genetics, 2016)

Development and validation of the biobanking attitudes and knowledge survey-Spanish (BANKS-SP) - Mariana Arevalo; Paul B. Jacobsen; Clement K. Gwede; Cathy D. Meade; Gwendolyn P. Quinn; John S. Luque; Gloria San Miguel; Dale Watson; Kristen J. Wells (Journal of Community Genetics, 2016)

A Web-Based Platform for Educating Researchers About Bioethics and Biobanking - Ivana Sehovic; Clement K. Gwede; Cathy D. Meade; Stephen Sodeke; Rebecca Pentz; Gwendolyn P. Quinn (Journal of Cancer Education, 2016)

Discordance between nuclear and mitochondrial DNA analyses of population structure in closely related triplefin fishes (Forsterygion lapillum and F. capito, F. Tripterygiidae) supports speciation with gene flow - M. Rabone; S. D. Lavery; A. Little; K. D. Clements (Marine Biology, 2015)

Patients’ Perceptions of Colorectal Cancer Screening Tests and Preparatory Education in Federally Qualified Health Centers - Clement K. Gwede; Alexis M. Koskan; Gwendolyn P. Quinn; Stacy N. Davis; Jamila Ealey; Rania Abdulla; Susan T. Vadaparampil; Gloria Elliott; Diana Lopez; David Shibata; Richard G. Roetzheim; Cathy D. Meade (Journal of Cancer Education, 2015)

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

Dynamic social networks in guppies (Poecilia reticulata) - Alexander D. M. Wilson; Stefan Krause; Richard James; Darren P. Croft; Indar W. Ramnarine; Karoline K. Borner; Romain J. G. Clement; Jens Krause (Behavioral Ecology and Sociobiology, 2014)

Effectiveness of fishing gears to assess fish assemblage size structure in small lake ecosystems - T. A. Clement; K. Pangle; D. G. Uzarski; B. A. Murry (Fisheries Management and Ecology, 2014)
Measurement of fish body‐size distributions is increasingly used as a management tool to assess fishery status. However, the effects of gear selection on observed fish size structure has not received sufficient attention. Four different gear types (experimental gill nets, fine mesh bag seine, and two different sized mesh trap nets), which are commonly employed in the study area for fisheries surveys, were used to fish in five small (

Journal Clubs: An Educational Approach to Advance Understanding Among Community Partners and Academic Researchers About CBPR and Cancer Health Disparities - Susan T. Vadaparampil; Vani N. Simmons; Ji-Hyun Lee; Teri Malo; Lynne Klasko; Maria Rodriguez; Rhonda Waddell; Clement K. Gwede; Cathy D. Meade (Journal of Cancer Education, 2014)

Making It Work: Health Care Provider Perspectives on Strategies to Increase Colorectal Cancer Screening in Federally Qualified Health Centers - Clement K. Gwede; Stacy N. Davis; Gwendolyn P. Quinn; Alexis M. Koskan; Jamila Ealey; Rania Abdulla; Susan T. Vadaparampil; Gloria Elliott; Diana Lopez; David Shibata; Richard G. Roetzheim; Cathy D. Meade (Journal of Cancer Education, 2013)

Early Postnatal Ethanol Exposure: Glutamatergic Excitotoxic Cell Death During Acute Withdrawal - K. M. Clements; L. M. Smith; J. N. J. Reynolds; P. G. Overton; J. D. Thomas; R. M. Napper (Neurophysiology, 2012)

Formative Research on Perceptions of Biobanking: What Community Members Think - John S. Luque; Gwendolyn P. Quinn; Francisco A. Montel-Ishino; Mariana Arevalo; Shalanda A. Bynum; Shalewa Noel-Thomas; Kristen J. Wells; Clement K. Gwede; Cathy D. Meade (Journal of Cancer Education, 2012)

Population structure and migration pattern of a conifer pathogen, Grosmannia clavigera , as influenced by its symbiont, the mountain pine beetle - CLEMENT K. M. TSUI; AMANDA D. ROE; YOUSRY A. EL‐KASSABY; ADRIANNE V. RICE; SEPIDEH M. ALAMOUTI; FELIX A. H. SPERLING; JANICE E. K. COOKE; JÖRG BOHLMANN; RICHARD C. HAMELIN (Molecular Ecology, 2012)
We investigated the population structure of Grosmannia clavigera (Gc), a fungal symbiont of the mountain pine beetle (MPB) that plays a crucial role in the establishment and reproductive success of this pathogen. This insect–fungal complex has destroyed over 16 million ha of lodgepole pine forests in Canada, the largest MPB epidemic in recorded history. During this current epidemic, MPB has expanded its range beyond historically recorded boundaries, both northward and eastward, and has now reached the jack pine of Alberta, potentially threatening the Canadian boreal forest. To better understand the dynamics between the beetle and its fungal symbiont, we sampled 19 populations in western North America and genotyped individuals from these populations with eight microsatellite markers. The fungus displayed high haplotype diversity, with over 250 unique haplotypes observed in 335 single spore isolates. Linkage equilibria in 13 of the 19 populations suggested that the fungus reproduces sexually. Bayesian clustering and distance analyses identified four genetic clusters that corresponded to four major geographical regions, which suggested that the epidemic arose from multiple geographical sources. A genetic cluster north of the Rocky Mountains, where the MPB has recently become established, experienced a population bottleneck, probably as a result of the recent range expansion. The two genetic clusters located north and west of the Rocky Mountains contained many fungal isolates admixed from all populations, possibly due to the massive movement of MPB during the epidemic. The general agreement in north–south differentiation of MPB and G. clavigera populations points to the fungal pathogen’s dependence on the movement of its insect vector. In addition, the patterns of diversity and the individual assignment tests of the fungal associate suggest that migration across the Rocky Mountains occurred via a northeastern corridor, in accordance with meteorological patterns and observation of MPB movement data. Our results highlight the potential of this pathogen for both expansion and sexual reproduction, and also identify some possible barriers to gene flow. Understanding the ecological and evolutionary dynamics of this fungus–beetle association is important for the modelling and prediction of MPB epidemics.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Enhancing Oncology Health Care Provider's Sensitivity to Cultural Communication to Reduce Cancer Disparities: A Pilot Study - Gwendolyn P. Quinn; Julio Jimenez; Cathy D. Meade; Teresita Muñoz-Antonia; Clement K. Gwede; Eida Castro; Susan T. Vadaparampil; Vani Nath Simmons; Jessica McIntyre; Theresa T. Crocker; Thomas H. Brandon (Journal of Cancer Education, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Characterization of the carbon fluxes of a vegetated drained lake basin chronosequence on the Alaskan Arctic Coastal Plain - D. ZONA; W. C. OECHEL; K. M. PETERSON; R. J. CLEMENTS; K. T. PAW U; S. L. USTIN (Global Change Biology, 2010)
Greenhouse gas fluxes from vegetated drained lake basins have been largely unstudied, although these land features constitute up to 47% of the land cover in the Arctic Coastal Plain in northern Alaska. To describe current and to better predict future sink/source activity of the Arctic tundra, it is important to assess these vegetated drained lake basins with respect to the patterns of and controls on gross primary production (GPP), net ecosystem exchange, and ecosystem respiration (ER). We measured CO 2 fluxes and key environmental variables during the 2007 growing season (June through August) in 12 vegetated drained lake basins representing three age classes (young, drained about 50 years ago; medium, drained between 50 and 300 years ago; and old, drained between 300 and 2000 years ago, as determined by Hinkel et al. , 2003) in the Arctic Coastal Plain. Young vegetated drained lake basins had both the highest average GPP over the summer (11.4 gCO 2 m −2 day −1 ) and the highest average summer ER (7.3 gCO 2 m −2 day −1 ), while medium and old vegetated drained lake basins showed lower and similar GPP (7.9 and 7.2 gCO 2 m −2 day −1 , respectively), and ER (5.2 and 4 gCO 2 m −2 day −1 , respectively). Productivity decreases with age as nutrients are locked up in living plant material and dead organic matter. However, we showed that old vegetated drained lakes basins maintained relatively high productivity because of the increased development of ice‐wedge polygons, the formation of ponds, and the re‐establishment of very productive species. Comparison of the seasonal CO 2 fluxes and concomitant environmental factors over this chronosequence provides the basis for better understanding the patterns and controls on CO 2 flux across the coastal plain of the North Slope of Alaska and for more accurately estimating current and future contribution of the Arctic to the global carbon budget.

Trophic ecology of New Zealand triplefin fishes (Family Tripterygiidae) - David A. Feary; M. Wellenreuther; K. D. Clements (Marine Biology, 2009)

Habitat use by triplefin species (Tripterygiidae) on rocky reefs in New Zealand - D. A. Feary; K. D. Clements (Journal of Fish Biology, 2006)
Habitat use and nesting sites of 12 triplefin species (Tripterygiidae) were investigated at 26 coastal and offshore rocky reef locations in north‐eastern New Zealand. Within these locations, 17 broad‐scale habitats and 14 fine‐scale habitats were surveyed using visual transects. In terms of broad‐scale habitat use, four species, Notoclinops segmentatus , Forsterygion lapillum , Forsterygion varium and Ruanoho whero showed a high similarity in distribution, irrespective of depth or habitat characteristics. The distributions of Bellapiscis lesleyae , Cryptichthys jojettae and Ruanoho decemdigitatus were relatively similar, being primarily confined to shallow habitats providing a high degree of shelter. Forsterygion flavonigrum , Forsterygion malcolmi and Notoclinops caerulepunctus were all predominantly found beyond 10 m, irrespective of habitat characteristics. Despite the majority of species using several distinct fine‐scale habitats, a high degree of variation was apparent between species, with the majority of species showing extremely low overlap of fine‐scale habitats used. Differences in fine‐scale habitat use were not apparent when comparing the nesting sites of species. All nests were found in fine‐scale habitats, presumably affording a high degree of shelter from predation and physical disturbance. Interspecific partitioning of spatial resources probably occurs by depth and microhabitat in this species assemblage in north‐eastern New Zealand.

Quality analysis applied on eddy covariance measurements at complex forest sites using footprint modelling - C. Rebmann; M. Göckede; T. Foken; M. Aubinet; M. Aurela; P. Berbigier; C. Bernhofer; N. Buchmann; A. Carrara; A. Cescatti; R. Ceulemans; R. Clement; et al. (Theoretical and Applied Climatology, 2005)

Prevalence of interspecific hybrids amongst asexual fungal endophytes of grasses - C. D. Moon; K. D. Craven; A. Leuchtmann; S. L. Clement; C. L. Schardl (Molecular Ecology, 2004)
Epichloë endophytes are fungal symbionts of grasses that span a continuum including asexual mutualists that are vertically transmitted, obligately sexual pathogens that are horizontally transmitted, and mixed‐strategy symbionts with both mutualistic and pathogenic capabilities. Here we show that processes of genome evolution differ markedly for the different symbiont types. Genetic and phylogenetic analysis was conducted of a broad taxonomic, ecological and geographical sample of sexual and asexual isolates, in which were identified and sequenced alleles of genes for β‐tubulin ( tub2 ) and translation elongation factor 1‐α ( tef1 ), and microsatellite alleles were identified by length polymorphisms. The majority of asexual isolates had two or three alleles of most loci, but every sexual isolate had only single alleles for each locus. Phylogenetic analysis of tub2 and tef1 indicated that in all instances of multiple alleles in an isolate, the alleles were derived from different sexual species. It is concluded that, whereas horizontally transmissible species had haploid genomes and speciation occurred cladistically, most of the strictly seedborne mutualists were interspecific hybrids with heteroploid (aneuploid or polyploid) genomes. Furthermore, the phylogenetic evidence indicated that, in at least some instances, hybridization followed rather than caused evolution of the strictly seedborne habit. Therefore, the abundance of hybrid species among grass endophytes, and their prevalence in many host populations suggests a selective advantage of hybridization for the mutualistic endophytes.

A new cacao linkage map based on codominant markers: development and integration of 201 new microsatellite markers - T. Pugh; O. Fouet; A. M. Risterucci; P. Brottier; M. Abouladze; C. Deletrez; B. Courtois; D. Clement; P. Larmande; J. A. K. N’Goran; C. Lanaud (Theoretical and Applied Genetics, 2004)

Key metabolic enzymes and muscle structure in triplefin fishes (Tripterygiidae): a phylogenetic comparison - A. J. R. Hickey; K. D. Clements (Journal of Comparative Physiology B, 2003)

Diet and endogenous carbohydrases in the temperate marine herbivorous fish Kyphosus sydneyanus - D. Moran; K. D. Clements (Journal of Fish Biology, 2002)
Stomach content analysis showed that Kyphosus sydneyanus collected by spearing from coastal reefs near Leigh, north‐east New Zealand, is herbivorous throughout its post‐settlement life. All size classes collected consumed a wide range of macroalgae, predominantly the phaeophytes Carpophyllum maschalocarpum and Ecklonia radiata , and the rhodophytes Gigartina macrocarpa and Caulacanthus ustulatus . Multivariate analysis of variance and discriminant function analysis showed an ontogenetic diet shift, with gut contents dominated by rhodophytes and chlorophytes in juveniles and by phaeophytes in adults. No significant seasonal variation in diet was apparent for any size class. Amylase and amylopectinase activity was highest in the smaller size classes. Laminarinase activity was relatively low throughout all size classes, and did not correlate with the ontogenetic increase in phaeophyte consumption. The activity of endogenous enzymes hydrolysing starch broadly correlated with rhodophyte consumption in adult specimens of three other species of marine herbivorous fishes: Odax pullus, Girella tricuspidata and Parma alboscapularis; laminarin hydrolysis, however, was negatively correlated with phaeophyte consumption. Overall, the diet and enzyme results suggest that juvenile K. sydneyanus rely mainly on the endogenous digestion of rhodophytes and chlorophytes, while exogenous (microbial) digestion is used to digest the phaeophyte‐dominated diet of adults.

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.

TCS: a computer program to estimate gene genealogies - M. Clement; D. Posada; K. A. Crandall (Molecular Ecology, 2000)

Haemoglobin components and oxygen transport in relation to habitat distribution in triplefin fishes (Tripterygiidae) - O. Brix; K. D. Clements; R. M. G. Wells (Journal of Comparative Physiology B, 1999)

Ceratobium mosaic potyvirus: another virus from orchids - A. M. Mackenzie; M Nolan; K.-J. Wei; M. A. Clements; D. Gowanlock; B. J. Wallace; A. J. Gibbs (Archives of Virology, 1998)

Preservation of inherent contractility in isolated gut segments from herbivorous and carnivorous marine fish - K. D. Clements; D. Rees (Journal of Comparative Physiology B, 1998)

Comparison of herbivory in the closely-related marine fish genera Girella and Kyphosus - K. D. Clements; J. H. Choat (Marine Biology, 1997)